Structure and magnetism in LaCoO3. (11th December 2015) - Belanger, D P; Keiber, T; Bridges, F; Durand, A M; Mehta, A; Zheng, H; Mitchell, J F; Borzenets, V
Abstract: The temperature dependence of the hexagonal lattice parameter c of single crystal (LCO) with H   =  0 and 800 Oe, as well as LCO bulk powders with H   =  0, was measured using high-resolution x-ray scattering near the transition temperature K. The change of c ( T ) is well characterized by a power law in for and by a temperature independent constant for when convoluted with a Gaussian function of width 8.5 K. This behavior is discussed in the context of the unusual magnetic behavior observed in LCO as well as recent generalized gradient approximation calculations.